Role of echocardiography in acute stroke patients admitted to ICU - Lokesh SB; Latha V (Asian Journal of Medical Sciences)
Background: Stroke is gaining worldwide importance as the focus now shifts to non-communicable diseases. The etiological investigation of the potential cardiac source of acute ischemic stroke (AIS) is important for the secondary prevention of recurrent and future embolization and also helps in finding other etiology.